2010
DOI: 10.1111/j.1365-2109.2010.02490.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein-, peptide- and free amino acid-based diets in fish nutrition

Abstract: In the present review, we summarize data related to the utilization of purified diets formulated with the purpose of determining the amino acid requirements in fish independent of the ontogenetic stage and the morphological characteristics of the digestive tract. Expanding present knowledge on the formulation of protein, free amino acid (FAA) and synthetic dipeptide‐based diets can provide possible insights that might lead to a better understanding of the mechanism of amino acid utilization in the growth of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…It is possible that the lysine added to the diets was not well absorbed by salmon, as crystalline amino acids may be absorbed at a different rate than protein-bound amino acids, which can reduce the efficiency of uptake (Peres & Oliva-Teles 2005) and ultimately affect the growth performance (Dabrowski et al 2010). Weight gain and specific growth rate are centred in the plot and closely located to glycine, tyrosine, leucine and 16:1n-7.…”
Section: Aquaculture Nutritionmentioning
confidence: 99%
“…It is possible that the lysine added to the diets was not well absorbed by salmon, as crystalline amino acids may be absorbed at a different rate than protein-bound amino acids, which can reduce the efficiency of uptake (Peres & Oliva-Teles 2005) and ultimately affect the growth performance (Dabrowski et al 2010). Weight gain and specific growth rate are centred in the plot and closely located to glycine, tyrosine, leucine and 16:1n-7.…”
Section: Aquaculture Nutritionmentioning
confidence: 99%
“…; Dabrowski et al . ). This was attributed to differences in free AA and protein‐bound AA absorption rates in the intestine or leaching of AA from the feed (Peres & Oliva‐Teles ).…”
Section: Discussionmentioning
confidence: 97%
“…However, similarly to the present study, a dietary replacement of protein-bound by crystalline-AA up to 45% in gilthead seabream (Marcouli et al 2004) or 50% in rainbow trout (Rodehutscord et al 1995;Bodin et al 2012) was achievable without affecting fish . performances. Differently, other studies in fish indicated that comparatively with protein-bound amino acids including crystalline-AA in diet formulation negatively affects fish performance (Cowey 1992;Zarate & Lovell 1997;El-Haroun & Bureau 2007;Hauler et al 2007;Dabrowski et al 2010). This was attributed to differences in free AA and protein-bound AA absorption rates in the intestine or leaching of AA from the feed (Peres & Oliva-Teles 2005).…”
Section: Aquaculture Nutritionmentioning
confidence: 98%
“…In our study, the FCR increased and PER reduced while the supplement levels of CPH improved in diets. Studies have shown that gastrointestinal absorption rate asynchronism between free amino acids and protein‐bound amino acids can lead to the lower bio‐efficacy values of free amino acids contained in protein hydrolysate (Ambardekar, Reigh, & Williams, ; Bodin et al., ; Dabrowski, Zhang, Kwasek, Hliwa, & Ostaszewska, ; Espe, Lied, & Torrissen, ; Espe, Sveier, Høgøy, & Lied, ; Nunes, Sá, Browdy, & Vazquez‐Anon, ; Zarate, Lovell, & Payne, ), whereas the reduction in feed utilization could be offset to some extent with an increase in FI. The present study showed a significant enhancement of FI in turtle fed with diet CPH15.…”
Section: Discussionmentioning
confidence: 99%